Question
upstudy study bank question image url

c) \( y=-2 e^{3 x}+\sqrt{e} \)

Ask by Cruz Moreno. in the United States
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The function \( y = -2 e^{3x} + \sqrt{e} \) has the following features: - **Domain:** All real numbers. - **Range:** From negative infinity to \( \sqrt{e} \). - **y-intercept:** \( \sqrt{e} - 2 \). - **x-intercept:** \( \frac{1}{3} \ln\left(\frac{\sqrt{e}}{2}\right) \). - **Asymptote:** Horizontal at \( y = \sqrt{e} \).

Solution

To analyze the function \( y = -2 e^{3x} + \sqrt{e} \), we can explore its features such as its domain, range, intercepts, and asymptotic behavior. ### Step 1: Determine the Domain The domain of the function is the set of all possible values of \( x \) for which the function is defined. Since the exponential function \( e^{3x} \) is defined for all real numbers, the domain of \( y \) is: \[ \text{Domain: } (-\infty, \infty) \] ### Step 2: Determine the Range To find the range, we need to analyze the behavior of the function as \( x \) approaches positive and negative infinity. - As \( x \to -\infty \): \[ e^{3x} \to 0 \implies y \to -2(0) + \sqrt{e} = \sqrt{e} \] - As \( x \to \infty \): \[ e^{3x} \to \infty \implies y \to -2(\infty) + \sqrt{e} = -\infty \] Thus, the function decreases from \( \sqrt{e} \) to \( -\infty \). Therefore, the range is: \[ \text{Range: } (-\infty, \sqrt{e}] \] ### Step 3: Find the Intercepts #### y-intercept: To find the y-intercept, set \( x = 0 \): \[ y(0) = -2 e^{3(0)} + \sqrt{e} = -2(1) + \sqrt{e} = \sqrt{e} - 2 \] #### x-intercept: To find the x-intercept, set \( y = 0 \): \[ 0 = -2 e^{3x} + \sqrt{e} \] \[ 2 e^{3x} = \sqrt{e} \] \[ e^{3x} = \frac{\sqrt{e}}{2} \] Taking the natural logarithm of both sides: \[ 3x = \ln\left(\frac{\sqrt{e}}{2}\right) \] \[ x = \frac{1}{3} \ln\left(\frac{\sqrt{e}}{2}\right) \] ### Step 4: Asymptotic Behavior As \( x \to -\infty \), \( y \to \sqrt{e} \) (horizontal asymptote). As \( x \to \infty \), \( y \to -\infty \). ### Summary of Features - **Domain:** \( (-\infty, \infty) \) - **Range:** \( (-\infty, \sqrt{e}] \) - **y-intercept:** \( \sqrt{e} - 2 \) - **x-intercept:** \( \frac{1}{3} \ln\left(\frac{\sqrt{e}}{2}\right) \) - **Horizontal asymptote:** \( y = \sqrt{e} \) If you need further analysis or specific calculations, please let me know!

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

Did you know that the exponential function, like \( e^{3x} \), is continuously increasing? This means that as \( x \) gets larger, \( y \) will grow rapidly in magnitude due to the exponent. In this case, the negative coefficient before the exponential function indicates that the curve will descend steeply, providing a fun rollercoaster-like experience for your graph! If you've got \( y = -2 e^{3x} + \sqrt{e} \), a common mistake when interpreting the graph is overlooking the influence of the exponential term. The \( -2 e^{3x} \) will dominate as \( x \) increases, pulling \( y \) downward, while \( \sqrt{e} \) simply lifts the whole function up slightly, creating an interesting offset. Always double-check how each term impacts the overall behavior!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy